Pengendalian Kualitas pada Industri Kerajinan Sarung Tangan dengan Metode Six Sigma dan FMEA pada CV. XYZ - Yosua, Yosua; Susetyo, Agustinus Eko; Susanti, Dyah Ari (Industrika : Jurnal Ilmiah Teknik Industri, 2024)
XYZ is a company that produces gloves. Due to the resulting defects such as vague logos, slanted stitching, mold and loose stitching, the company needs to make quality improvements so that defects become 0%. The aim of this research is to carry out quality control using the Six Sigma and FMEA methods to determine the sigma value and determine the causes of defects and make recommendations for improvements to the highest defects. From the results of Six Sigma calculations, a sigma level of 3.6 was obtained, which means that it is sufficient and 197,300 defects can occur on a production scale of one million. The capability results with an average value of 1.15 indicate that it is only quite reliable on a scale of 1-2. FMEA shows the highest cause of failure is sewing machine jams which can cause skewed stitches. The recommended control plan is to carry out routine weekly machine maintenance. Common factors causing defects are lack of regular maintenance on production machines, worker negligence, worker fatigue due to hot weather, lack of strict supervision of workers during the production process, less skilled workers and humid air temperatures resulting in moldy gloves. Proposed improvements in overcoming defects include carrying out routine maintenance on all machines, carrying out strict supervision of workers, implementing SOPs with strict supervision, adding air conditioning facilities, and adding a sterilization process for finished glove products. Keywords: DMAIC, FMEA, Six Sigma